Drowning in a Sea of News: The Role of Doomscrolling, News Overload, and News Failure in the Relationship Between News Search on Social Media and News Avoidance in Natural Disaster Situations - Koselioren, Mihrali; Cakir, Cihan (Routledge Journals, Taylor & Francis Ltd, 2024)
Turkiye is a region prone to earthquakes, and its fault structures generate destructive earthquakes on a regular basis. In this sense, a second devastating earthquake occurred in February 2023, and a great deal of information and news about it was distributed, particularly on social media. In cases of natural disasters such as earthquakes, this study examines the effect of intense and negative news flow on news avoidance as a consequence of people's search for information about the event on social media. In this regard, a survey was conducted with the participation of 398 social media users in Istanbul, the most populous and earthquake-prone city in Turkiye, during the months of March and April. As a result of the study, it has been determined that there is a direct effect between information seeking on social media and news avoidance, whereas there is an indirect mediation effect between doomscrolling, news overload, and news fatigue. In addition, as the age and educational level of the participants increase, while being affected by doomscrolling, news overload, news fatigue, and news avoidance variables decrease, there is no significant difference in the category of information seeking on social media.
Keywords: Information seeking; social media; doomscrolling; news overload; news fatigue; news avoidance